DETERMINANT OF PURCHASE DECISIONS AT PT. TIRTA EMAS KEMASINDO - ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
The goal of this study is to determine the determinant of purchasing decisions for drinking water in the Jesslyn brand at PT. Tirta Emas Kemasindo Pekanbaru. The population in this research are consumers of PT. Tirta Emas Kemasindo Pekanbaru, where they purchase bottled drinking water products. The sampling method was an Accidental Sampling with a sample of 100 consumers costumers made up of department stores, supermarkets, store, and kiosks that sell bottled drinking water undder Jesslyn brand. Data analysis used is multiple linear regression. The result of the hypothesis that product quality, price, and promotion have a significant effect on purchasing decisions, while location does not have a significant influence on purchasing decisions for drinking water in the Jesslyn brand at PT. Tirta Emas Kemasindo